If he made 25 percent profit, the selling price (1200 naira) is 125 percent.
If 125% is equal to 1200 naira
100 percent (the original) will be 100 × 1200 divided by 125
Which is 120000 ÷ 125
Therefore, the cost price is 960 naira
Sqrt(1-3x)=x+3
[sqrt(1-3x)]^2=(x+3)^2
1-3x=(x+3)(x+3)
1-3x=x^2+6x+9
-3x=x^2+6x+8
0=x^2+9x+8
The answers are -1 and -8 BUT, we have to plug them back into the original equation to make sure we don't get a negative under the square root sign.
After doing this, we realize that only -1 works, so the answer is x=-1
Sorry that this took forever to answer. I was thinking of a good way to explain this, and if you need any further explanation, message me:)
Best wishes:)
Solutions
<span>To solve the problem our first step is to find the prime factorization of each number. </span>
4 = 2²
<span>5 = 5 </span>
<span>6 = 2 x 3
</span>
Calculations
<span>LCM = 2² x 3 x 5 = 60 </span>
Answer:
downwards
Step-by-step explanation:
the equation of a parabola in vertex form is
f(x) = a(x - h)² + k
where (h, k ) are the coordinates of the vertex and a is a multiplier
• if a > 0 then parabola opens upwards
• if a < 0 then parabola opens downwards
for
f(x) = - 4(x - 3)² + 9 with a = - 4 < 0 , then
the parabola opens downwards
Hey there :)
- tan²x + sec²x = 1 or 1 + tan²x = sec²x
sin²x + cos²x = 1
Divide the whole by cos²x
![\frac{sin^2x}{cos^2x} + \frac{cos^2x}{cos^2x} = \frac{1}{cos^2x}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bsin%5E2x%7D%7Bcos%5E2x%7D%20%2B%20%5Cfrac%7Bcos%5E2x%7D%7Bcos%5E2x%7D%20%3D%20%5Cfrac%7B1%7D%7Bcos%5E2x%7D%20)
![\frac{sinx}{cosx} = tanx](https://tex.z-dn.net/?f=%20%5Cfrac%7Bsinx%7D%7Bcosx%7D%20%3D%20tanx)
so
![\frac{sin^2x}{cos^2x} = tan^2x](https://tex.z-dn.net/?f=%20%5Cfrac%7Bsin%5E2x%7D%7Bcos%5E2x%7D%20%3D%20tan%5E2x)
and
![\frac{1}{cosx} = secx](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7Bcosx%7D%20%3D%20secx%20)
so
![\frac{1}{cos^2x} = sec^2x](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7Bcos%5E2x%7D%20%3D%20sec%5E2x)
Therefore,
tan²x + 1 = sec²x
Take tan²x to the other side {You will have the same answer}
1 = - tan²x = sec²x or sec²x - tanx = 1